Smart and Sustainable Initiatives in Legal Amazon Cities - Lima, Thamires Barroso; Santos, Marcelo Cássio Lima; Meira, Celso Maciel de; Ramos, Heidy Rodriguez; Gallardo, Amarilis Lucia Casteli Figueiredo (Technical and Scientific Journal Green Cities, 2024)
The themes of smart and sustainable cities, known as "smart cities," represent a contemporary research field focused on the application of innovative technologies aimed at improving the quality of life for urban residents harmonizing within the principles of sustainability. This study aims to identify intelligent and sustainable initiatives adopted in different cities within the Legal Amazon. To achieve this, a systematic literature review was conducted to map successfully implemented actions in cities with populations exceeding 500,000 inhabitants. The identified initiatives emphasize the interconnection between social, environmental, and economic dimensions, focusing on technological innovation, urban and energy planning, as well as promoting better quality of life, reducing domestic violence rates, mitigating social inequalities, promoting social inclusion, and ensuring environmental sustainability. Consequently, it is expected that the results achieved can contribute to the implementation of more effective public policies in the Legal Amazon, empowering public managers to make informed decisions aligned with the specific challenges and opportunities of the region.